Duality of teaching roles and teaching effectiveness - Cular, Anita Garrido (Danyag :the UPV journal of humanities and social sciences, 2000)
This is a study in four State Colleges and Universities in Region 8 that focused on teaching effectiveness vis-a-vis certain variables: the different academic roles of teachers (teaching, research, extension and administrative work); teacher-related variables (age, civil status, etc.) as well as institutional-related variables (entrance examinations, teaching load, etc.). With 153 teachers as respondents, measures of correlation and analysis of variance were used to establish the relationship.